PENINGKATAN KUALITAS SUMBER DAYA MANUSIA (SDM) PETANI PADI SAWAH - Ibrahim Ibrahim; Ahmad AC; Akhmad Akhmad (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2021)
This research aims to find and find the right and effective way to improve the cauldron of human resources (HR) of rice paddy farmers through agricultural extension methods. The research method used is qualitative research that is descriptive with data collection techniques through observation, interviews, documentation and other data that support research. The results showed that the most appropriate and effective method of agricultural extension towards improving the quality of human resources (HR) of rice paddy farmers is Demplot and Field School because of its informal nature, the learning process is carried out in the field where there are real objects in the form of rice plants that are used as learning materials, the implementation is done by providing guidance then invited directly to the field to see and do joints. Ri by looking at the examples given by extensionists, so that farmers more easily absorb it. With the real evidence seen by farmers, this field school was able to change the mindset of farmers who initially tried to farm in the traditional way then become farmers who follow innovative technology. This method lasted about 4 months or 1 growing season. Keywords: Quality, Extension Methods, Farmer Groups